Effect of Performance Appraisal, Work Culture, and Incentives On Employee Performance In Healthcare Services - Gusti A. Wahyudi; Azwardi; Sasti Ferina, Ika (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of performance appraisal, work culture, and incentives on employee performance at Rumah Sakit Bukit Asam Medika (RSBAM). Using a quantitative approach and causal research design, data were collected from 215 employees through a census method and analyzed using multiple linear regression. The results reveal that performance appraisal, work culture, and incentives positively and significantly affect employee performance. Work culture is identified as the most influential factor. These findings suggest that strengthening organizational culture, supported by an objective performance appraisal system and performance-based incentive programs, can enhance employee performance and improve the quality of hospital services.